2009
DOI: 10.1002/adfm.200900801
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and Photocurrent Generation in Polythiophene/Polyfluorene Copolymer Blends

Abstract: Here, studies on the evolution of photophysics and device performance with annealing of blends of poly(3‐hexylthiophene) with the two polyfluorene copolymers poly((9,9‐dioctylfluorene)‐2,7‐diyl‐alt‐[4,7‐bis(3‐hexylthien‐5‐yl)‐2,1,3‐benzothiadiazole]‐2′,2′′‐diyl) (F8TBT) and poly(9,9‐dioctylfluorene‐co‐benzothiadiazole) (F8BT) are reported. In blends with F8TBT, P3HT is found to reorganize at low annealing temperatures (100 °C or below), evidenced by a redshift of both absorption and photoluminescence (PL), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 31 publications
8
114
0
Order By: Relevance
“…[40] In addition to the V oc , the EQE and J sc also improved after post-thermal annealing. For P3HT:PCBM and P3HT:F8TBT, thermal annealing alone can effectively increase P3HT crystalline order similar to using additives, [2,14] and the EQE with only post-thermal annealing here was slightly higher than with only additive processing. However, a combination of solvent additives and post-annealing led to even greater improvement than applying either process alone, and the hole mobility in the near saturation at negative biases, where charge separation and extraction are facilitated by a high internal field, suggests that more efficient exciton dissociation is an important factor for the ordering in this blend.…”
mentioning
confidence: 75%
“…[40] In addition to the V oc , the EQE and J sc also improved after post-thermal annealing. For P3HT:PCBM and P3HT:F8TBT, thermal annealing alone can effectively increase P3HT crystalline order similar to using additives, [2,14] and the EQE with only post-thermal annealing here was slightly higher than with only additive processing. However, a combination of solvent additives and post-annealing led to even greater improvement than applying either process alone, and the hole mobility in the near saturation at negative biases, where charge separation and extraction are facilitated by a high internal field, suggests that more efficient exciton dissociation is an important factor for the ordering in this blend.…”
mentioning
confidence: 75%
“…For the unannealed device, charge carrier density starts to decrease at relatively high temperatures, indicating less efficient charge separation. For the P3HT∶F8TBT device, the charge carrier density already decreases from RT, meaning that charge separation limits V OC even at RT [38].…”
mentioning
confidence: 99%
“…In particular, a PCE up to 1.8 % and extremely high V oc over 1 V were recorded for the optimized F8TBT/ P3HT-based PSC device. Further studies by McNeill et al [177] demonstrated that the relatively low efficiency of the P3HT/F8BT system can be attributed to poor charge generation and separation efficiencies which result from the failure of P3HT reorganization.…”
Section: Conjugated Polymer Acceptor Materialsmentioning
confidence: 97%